Vpliv slovenskih lepotnih blogov na nakupno namero generacije mlajših milenijcev - Hrovat, Neža (Akademija MM, 2018)
The development of the blogosphere in Slovenia, and globally, is increasingly marked by the trend known as the "commercialisation" of blogs. In consumers' eyes bloggers increasingly take on the role of influencers, who share their opinions or recommendations regarding specific products, brands or companies with their social network. Therefore, from the viewpoint of brand managers and companies at large the collaborations with bloggers and blogs, which represent a type of electronic word-of-mouth, are fast becoming an important part of planning their communication campaigns even though till now only little research has been done in relation to the impact of following blog content on consumers' behavioural intentions. In order to address this research gap, the present study examines the relationship between blog characteristics and their influence on the consumers' purchase, and it does so by focusing on analysing the Slovenian beauty bloggers and the generation of younger millennials as their primary target group. The study introduces an updated model for investigating the influence of electronic word-of-mouth on the purchase intention in the context of a blogosphere. The results of a quantitative study show that the blog content produced by Slovenian beauty bloggers affects the purchase intention of the generation of (younger) millennials. It is revealed that both the perceived credibility and the level of adoption of blog content - the latter is predicted both by the consumers' attitude towards information and the perceived usefulness of information - have a positive impact on the consumers' purchase intention. The study also examines some practical implications of research results for bloggers and companies that collaborate with them to pursue marketing goals.
Keywords: informacijska tehnologija; mladina; nakup; potrošniki; psihologija potrošnika; spletni dnevniki